DUALITY IN SMALL AND MEDIUM ENTERPRISE ACCOUNTING PRACTICES - Cahyaningtyas, Fadilla (Faculty of Economics and Business, University of Muhammadiyah Malang, 2017)
This research is aimed to comprehend the accounting practice and its benefit in triggering one of the most credible SMEs in Malang City to succeed, SME Garuda Jaya. The analytical tool used in this research is transcendental phenomenology. Based on data analysis, two kinds of accounting practices are: (1) accounting practice of mind and memory; and (2) accounting notation to the arrangement of basic financial statements in the form of balance sheets and Profit/ Loss (L / R). both practical accounting establishes duality practices, a practice that combines two distinct and different things into integral and appropriate things to do an accounting practice. Therefore, first, duality practices seek to make synergistic social and economic value. Second, the practice of duality establishes the integration of